2017
DOI: 10.1515/popore-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Radiation balance diversity on NW Spitsbergen in 2010–2014

Abstract: This article presents the results of observations of selected fluxes of the radiation balance in north-western Spitsbergen in the years from 2010 to 2014. Measurements were taken in Ny-Ålesund and in the area of Kaffiøyra, on different surface types occurring in the Polar zone: moraine, tundra, snow and ice. Substantial differences in the radiation balance among the various types of surface were observed. The observations carried out in the summer seasons of 2010-2014 in the area of Kaffiøyra demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The radiation paradox [51] was not observed on JRI, as the effect of cloudiness was to cool the ground surface and soil layer, since the decrease in Q S↓ was not compensated for by an increase in Q L↓ . Such conditions also occurred in summer on Svalbard [52]. For individual days, the difference in Q net and Q G , due to lower cloudiness on JRI, could have been up to 120 and 17.5 W m −2 , respectively, while the difference in Q net was only 100 W m −2 across the tundra in Svalbard [43].…”
Section: Snow Cover and Cloudiness Effectsmentioning
confidence: 82%
“…The radiation paradox [51] was not observed on JRI, as the effect of cloudiness was to cool the ground surface and soil layer, since the decrease in Q S↓ was not compensated for by an increase in Q L↓ . Such conditions also occurred in summer on Svalbard [52]. For individual days, the difference in Q net and Q G , due to lower cloudiness on JRI, could have been up to 120 and 17.5 W m −2 , respectively, while the difference in Q net was only 100 W m −2 across the tundra in Svalbard [43].…”
Section: Snow Cover and Cloudiness Effectsmentioning
confidence: 82%
“…The frontal moraines of the marine-terminating Aavatsmarkbreen are deposited on the bay bottom. (Kejna & Sobota, 2019, 2021.…”
Section: Study Area and Regional Settingmentioning
confidence: 99%
“…There it is associated not only with its aggradation in areas freed from ice but also partly with persistent subglacial permafrost (Alexander et al, 2020;Etzelmüller & Hagen, 2005;Sollid & Sørbel, 1994). The trend of constantly increasing average annual temperatures in Spitsbergen in recent decades, including in the research area (Kejna & Sobota, 2019, 2021, is causing a systematic deepening of the active layer (AL) thickness (ALT) of permafrost (Sobota et al, 2018). However, this process is not even over a larger area and is largely dependent on local factors such as morphology, sun exposure, duration of snow cover, and lithology and its related water content (Araźny & Grze s, 2000;Dobi nski & Kasprzak, 2022;Etzelmüller et al, 2011;Migała, 1991;Rachlewicz & Szczuci nski, 2008).…”
Section: Permafrost and Thermokarst Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Svalbard, direct glacio‐meteorological data sets extending for 5 or more years have been discussed in more detail for only two relatively large ice masses: Austfonna (7,800 km 2 ) and Kongsvegen (102 km 2 ) (Figure a) (e.g., Karner et al , ; Schuler et al , ). Boundary‐layer meteorology of small alpine glaciers of Svalbard, defined here as cirque and small valley glaciers (<20 km 2 ), remains even less discussed in the literature, with only a few exceptions from Midre Lovénbreen (Hodson et al , ) and Waldemarbreen (Kejna et al , ; ) (Figure a). Małecki () demonstrated that alpine glaciers represent an important component of the regional sea‐level rise contribution due to their strongly negative mass balance, despite their low overall area.…”
Section: Introductionmentioning
confidence: 99%